Перспективи та особливості розвитку жіночого підприємництва. - Prokopets, Liudmyla; Karp, Angelika (My University, 2021)
У статті розглянуто стан та особливості розвитку жіночого підприємництва в Україні. У нашій країні проблема "поділу за статевою ознакою" завжди мала місце і часто розвивалася в дискримінацію жінки, у применшення її прав. З проблемою "прихованої" дискримінації, безумовно, стикалася кожна жінка: роботодавці найчастіше вважають за краще не приймати на відповідальні посади жінок, мотивуючи це різними способами — це все розглядається в статі. Також досліджено частку жінок-керівників у різних сферах діяльності та типи підприємств, у яких домінують жінки-керівники. Розглянуті жіночий і чоловічий стиль ведення бізнесу. Розкрито гендерну мотивацію жінок до ведення підприємницького бізнесу. Дано оцінку сучасного стану жіночого підприємництва і показані шляхи усунення бар'єрів, що перешкоджають розвитку жіночого підприємництва.
Despite the rapid growth of women in professional and managerial work, the gender gap in entrepreneurship in Ukraine remains large. Women are less likely to start a new business than men, although the difference is starting to narrow. It is obvious that women's entrepreneurship is an intercultural phenomenon that has aspects specific to different cultures. The article considers the state and features of the development of women's entrepreneurship in Ukraine. In our country, the problem of "gender segregation" has always existed, and often developed into discrimination against women, in the reduction of her rights. Of course, every woman has faced the problem of "hidden" discrimination: employers often prefer not to hire women, motivating it in different ways — all this is considered in the article. The share of women managers in various fields of activity and types of enterprises dominated by women managers were also studied. The article considers women's entrepreneurship as one of the most effective areas of women's employment. The subject of entrepreneurial activity faces a special class of social problems: conflicts of roles played in public and private life, mass consciousness, deformation towards patriarchy and more. Inevitable in the transition to a market economy, structural adjustment requires a revision of conceptual and methodological approaches to the formation of women's entrepreneurship. It is a question of creation of favorable conditions for disclosure of creative potential of women. This is important not only for the formation of women's employment policy for the future, but also for solving current, sometimes quite acute problems of their career definition. Female and male business style are considered. The gender motivation of women to run a business is revealed. An assessment of the current state of women's entrepreneurship is given and ways to eliminate barriers to the development of women's entrepreneurship are shown. Women entrepreneurs need government support. In this case, support should be directed not to the company itself, but directly to the woman entrepreneur. After all, first of all women need the opportunity to believe in themselves, to see positive examples of other successful women entrepreneurs.
Keywords: жіноче підприємництво; жіночий стиль підприємництва; бізнесвумен; гендерна мотивація; стимулювання; women's entrepreneurship; women's business style; businesswoman; gender motivation; incentives